The proposal of model for building cooperation management in company - Soviar, Jakub; Vodák, Josef; Lendel, Viliam (Business: Theory and Practice, 2015)
The goal of the article is to use detailed literature analysis and findings of an empirical research, and to propose model for building cooperation management in a company. The article brings a valuable tool to company managers in a form of a complex and detailed model to achieve successful implementation of cooperation management in a company. The article thus provides a tool for company managers for managing their cooperation projects and activities. Use of this tool is meant to help minimize occurrence of conflict situations and to support smooth progress of cooperation activities.